2004
DOI: 10.1074/jbc.m404750200
|View full text |Cite
|
Sign up to set email alerts
|

Replication Protein A and the Mre11·Rad50·Nbs1 Complex Co-localize and Interact at Sites of Stalled Replication Forks

Abstract: In response to replicative stress, cells relocate and activate DNA repair and cell cycle arrest proteins such as replication protein A (RPA, a three subunit protein complex required for DNA replication and DNA repair) and the MRN complex (consisting of Mre11, Rad50, and Nbs1; involved in DNA double-strand break repair). There is increasing evidence that both of these complexes play a central role in DNA damage recognition, activation of cell cycle checkpoints, and DNA repair pathways. Here we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 46 publications
7
123
1
Order By: Relevance
“…71 A phospho-specific antibody for Nbs1 is known to be damage-dependent, and we previously showed that the phospho-RPA antibody is specific for the damage-induced hyperphosphorylated form of RPA-p34. 20 ETOP treatment led to the increase in all three phospho-proteins investigated as expected regardless of cell cycle phase (Fig. 4).…”
Section: Synchronization In S Phase Leads To Formation Of Rpa Focimentioning
confidence: 62%
See 1 more Smart Citation
“…71 A phospho-specific antibody for Nbs1 is known to be damage-dependent, and we previously showed that the phospho-RPA antibody is specific for the damage-induced hyperphosphorylated form of RPA-p34. 20 ETOP treatment led to the increase in all three phospho-proteins investigated as expected regardless of cell cycle phase (Fig. 4).…”
Section: Synchronization In S Phase Leads To Formation Of Rpa Focimentioning
confidence: 62%
“…4,[10][11][12][13][14][15][16][17][18][19][20][21] RPA is also hyperphosphorylated (particularly the p34 subunit) following DNA damage and replicative stress. [20][21][22][23] which is hypothesized to function as a "switch" to direct RPA activity from DNA replication to DNA repair. 9,24,25 The MRN complex is composed of Mre11, Rad50 and Nbs1.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of ATM or the MRN complex subunits results in embryonic lethality in eukaryotes (Xiao and Weaver, 1997;Luo et al, 1999;Zhu et al, 2001a) and hypomorphic mutations are associated with a variety of human disorders, including ataxia-telangiectasia (AT), ataxia-telangiectasia-like disorder (ATLD) and Nijmegen breakage syndrome (NBS, Carney et al, 1998;Matsuura et al, 1998;Varon et al, 1998;Stewart et al, 1999;Shiloh, 2006), suggesting their involvement during normal DNA replication. At the molecular level, the MRN complex associates with chromatin in an S phasespecific manner (Mirzoeva and Petrini, 2001) and binds with RPA (Robison et al, 2004;Olson et al, 2007). A similar phenomenon is evident in response to stalled replication forks.…”
Section: Dna Repair and Drug Resistancementioning
confidence: 72%
“…The nibrin͞Mre11͞Rad50 complex could be targeted to sites of action of AID by means of replication protein A, which can bind to Mre11 (29), and to AID (30). So far, the exact function of nibrin in class-switch recombination is not clear.…”
Section: Discussionmentioning
confidence: 99%